If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 15 + 6a + 6 = 0 Reorder the terms: 15 + 6 + 6a + 8x = 0 Combine like terms: 15 + 6 = 21 21 + 6a + 8x = 0 Solving 21 + 6a + 8x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + 6a + -21 + 8x = 0 + -21 Reorder the terms: 21 + -21 + 6a + 8x = 0 + -21 Combine like terms: 21 + -21 = 0 0 + 6a + 8x = 0 + -21 6a + 8x = 0 + -21 Combine like terms: 0 + -21 = -21 6a + 8x = -21 Add '-8x' to each side of the equation. 6a + 8x + -8x = -21 + -8x Combine like terms: 8x + -8x = 0 6a + 0 = -21 + -8x 6a = -21 + -8x Divide each side by '6'. a = -3.5 + -1.333333333x Simplifying a = -3.5 + -1.333333333x
| r^2-6r-4=0 | | 6x-15=4x-6 | | -3(9+4x)=-111 | | v=.33*256*17 | | 4x+22=12x+4 | | 17=x-1 | | -5(-1x+1)=35 | | 2x^2+4x+15=0 | | 4x+5+6x=-105 | | 4x+5+6x=-112 | | 4x+5+6x= | | 1/2= | | 6*x+4x+2x+2x+2x=900000 | | 24+x*5=4.14*(6+x) | | x^2+x*2+3=6 | | 24=-x+5x-4 | | 3x=7x-5 | | 3x-5=7X | | -1+3x+3x=5 | | 2c^2+7C+3= | | (2x-3)-9=0 | | 8(x-8)=2x-8 | | 3x+7+7x=37 | | 48-4x=5x+18 | | y=4x^2-5 | | 16s*16s+56s+49=0 | | 756845628-589= | | 8x+(5x-6-4x+1)=4x+(4x-1) | | 3x+6y= | | -111-77x=8x+24 | | (-4)-6x=-52 | | 12x-15=7x+50-7x |